Sosialisasi Pembuatan Nugget Tempe dalam Rangka Meningkatkan Gizi Anak di Polindes Desa Kampung Tengah Kabupaten Siak - Setyawatiningsih, Sri Catur; Ayun, Ulfi Kurrota; Romadhan, Novrialdi; Syahidah, Aqila Fakhira; Solihah, Restu; Aini, Janatul; Saragi, Taaj' Nidaa Febrian Br; Khairunnisa, Maulida; Muthmainnah, Andini; Marsya, Marsya; Simbolon, Fatimah Adinda Purnama; Indriani, R. Veni (LPPM UMRI, 2026)
Stunting is a chronic nutritional problem that affects children’s growth and development. One of its main causes is the lack of knowledge among mothers regarding balanced nutrition and proper feeding practices. Therefore, a community service program called GENTING (Movement for Education and Nutrition to Improve Child Nutrition) was conducted at the Polindes of Kampung Tengah Village, Mempura District, Siak Regency. This program aimed to provide practical education through demonstrations of making tempeh nuggets with moringa leaves as a nutritious food alternative. The methods included socialization, food processing demonstrations, distribution of educational posters, and evaluation using discussions and questionnaires. The results showed an increase in participants’ knowledge and skills in understanding children’s nutritional needs and preparing healthy meals independently. This program is expected to increase awareness among mothers in providing nutritious food as an effort to prevent stunting in the family environment.